(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
In our article, the essence of the legal creativity process, its importance in the development of society and the state, and its formation based on national and international experience are thoroughly analyzed. First of all, the constitutional foundations of the legal creativity process in the Republic of Uzbekistan, subjects implementing the right of legislative initiative, the increasing participation of the public, and the practical results of legal reforms are highlighted. The experience of legal creativity in foreign countries, including the principles of transparency, preliminary impact assessment, and priority of human rights applied in developing draft laws in European, US, Canadian, and Scandinavian states, are extensively examined.